Implementation of Sustainability Accounting in Improving Environmental Performance in the Hospitality Industry - OKTAVIA, Gusti Ayu Ardita Candra; SARI, Ni Kadek Purnama; PRADNYANI, Luh Gede Ratih; DEWI, Ni Putu Sinta; DEWI, Ni Komang Natalie Caksuni Putri (PT Batara Swastika Harati, 2025)
The hospitality industry is one of the sectors that greatly influences the economy in Indonesia globally through the development of tourism. There are many types of hotels, inns, and resorts spread across various regions in Indonesia that attract local and international tourists. However, despite the advantages presented by the hospitality industry today, there are negative impacts on the sustainability of social, economic, and especially environmental aspects. The approach and method used in this essay is a literature review method with a qualitative descriptive approach, where the phenomenon addressed in this essay is how the application of sustainability accounting in improving environmental performance in the hospitality industry is carried out. The results obtained from the case study at the Seminyak Bali Hotel show that sustainability accounting provides a framework for systematically identifying, measuring, and reporting environmental impacts and their financial implications. Successful initiatives, such as waste reduction and increased energy efficiency, lead to measurable environmental improvements and cost savings, which can be reported transparently. Despite challenges such as the lack of standard reporting guidelines, the increasing pressure for sustainable practices presents opportunities for the hospitality industry to minimize environmental impacts, maximize profits, and improve social welfare. Ultimately, integrating sustainability accounting into core business planning can lead to improved overall environmental performance in the hospitality sector.